Construction of disaster prevention capability evaluation framework of urban park system: methodology and its application in China - Fei, Wenjun; Wu, Jiyang; Shi, Ying; Chen, Qi (Journal of Environmental Engineering and Landscape Management, 2020)
The construction of disaster prevention capability evaluation framework is the basic requirement of building a sustainable and harmonious society under the background of urban public security. This study had constructed a framework for disaster prevention capability assessment of urban park systems applicable to China through rigorous logical reasoning and careful selection of indicators. The framework contains 4 first-level indicators and 8 second-level indicators and 21 third-level indicators. Quantitative methods and calculating procedures for each indicator and dynamic weight were also given in this paper. Finally, in order to prove the practical value of the evaluation system designed in this study, five cities in China were selected for application. The results showed that the indicator system can not only accurately quantify the disaster prevention capability of the urban park system, but also discover the shortcomings in the process of urban park system construction, which has strong theoretical and practical value.